Pembelajaran Berbasis Proyek dalam Pendidikan Agama Kristen: Meningkatkan Prestasi Siswa - Jepina Jepina; Yonatan Alex Arifianto (Sekolah Tinggi Teologi Kalvary - Maluku Utara, 2024)
Project-Based Learning in christian religious education is an innovative approach that is very effective in significantly improving student learning achievement. This method is used to encourage students to be actively involved in the learning process by using religious concepts with real projects in daily life. The purpose of this study is to explore the impact of the PBP model on students' understanding and skills in Christian Religious Education. Through the implementation of Project-Based Learning. Therefore, it can be concluded that the PBP strategy encourages students to be able to work together in groups and create relevant product results that are in accordance with Christian values, so that it can be said to be an effective alternative in Christian Religious Education which not only focuses on material understanding but also understanding in the formation of relevant holistic character and skills of students so that students become more interested. enthusiastic and enthusiastic in learning. The purpose of this study is to provide a deeper understanding and understanding of this Project-Based Learning method, the hope for teachers and educators to be able to design and design activities that are effective, fun and inspiring in supporting the development of students' spirituality in the context of Christianity.